2015
DOI: 10.1002/pc.23675
|View full text |Cite
|
Sign up to set email alerts
|

Polymericaly modified clays to preparation of polystyrene nanocomposite by nitroxide mediated radical polymerization and solution blending methods

Abstract: Polymericaly modified clays that contain an oligomeric poly (styrene-co-chloromethyl styrene) ammonium salt have been prepared and used to preparation of polystyrene (PS) nanocomposites. First, PS and poly(styrene-co-chloromethyl styrene) [P(St-co-CMSt)] were synthesized by nitroxide mediated living free radical polymerization (NMRP) by TEMPO iniferter .Then the copolymer was coupled with N, N-dimethyl hexadecyl amine to prepare polymeric modifier by anion exchange of chlorine group of chloromethyl styrene (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The resulting composite is a promising material for 3D-printing-based applications. Abbasian et al [64] employed well-defined, polymerically-modified clay nanoparticles for the preparation of PS composite by nitroxide-mediated radical polymerization and solution blending methods. This approach produced exfoliated or mixed intercalated/exfoliated composites.…”
Section: Solution-blending Methodsmentioning
confidence: 99%
“…The resulting composite is a promising material for 3D-printing-based applications. Abbasian et al [64] employed well-defined, polymerically-modified clay nanoparticles for the preparation of PS composite by nitroxide-mediated radical polymerization and solution blending methods. This approach produced exfoliated or mixed intercalated/exfoliated composites.…”
Section: Solution-blending Methodsmentioning
confidence: 99%
“…Combining nanoparticles with polymer matrix to form nanocomposites has been explored for decades, while blending is recognized as the most facile and direct approach [35]. Blending can be accomplished by several ways, including mechanical blending, melt blending, solution blending or emulsion blending, which mainly depends on the nature of polymer [36][37][38]. Nowadays, blending method has been extensively employed in the industry by relatively wider acceptance of inorganic particles with various shapes, sizes, or characters [35].…”
Section: Blendingmentioning
confidence: 99%
“…In these research works, it was confirmed that dispersion and arrangement of clay layers into PS matrix were greatly enhanced in the presence of several modifiers. 16 28 There are various types of block copolymers used for impact modification of PS, but commercially available styrene–butadiene–styrene (SBS) block copolymer is the most preferred candidate due to its ability to form distinct styrene (hard phase) and diene (rubber phase) domains with well-defined morphologies. Elastomeric character of SBS leads to improved mechanical ductility in addition to level up the compatibilization with an organoclay phase.…”
Section: Introductionmentioning
confidence: 99%